2021
DOI: 10.1016/j.apmr.2020.10.106
|View full text |Cite
|
Sign up to set email alerts
|

Personal Factors Associated With Postconcussion Symptoms 3 Months After Mild Traumatic Brain Injury

Abstract: To describe personal factors in patients with mild traumatic brain injury (MTBI) and 2 control groups and to explore how such factors were associated with postconcussion symptoms (PCSs). Design: Prospective cohort study. Setting: Level 1 trauma center and outpatient clinic. Participants: Participants (NZ541) included patients with MTBI (nZ378), trauma controls (nZ82), and community controls (nZ81). Main Outcome Measures: Data on preinjury health and work status, personality, resilience, attention deficit/hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
5
28
0
2
Order By: Relevance
“…Our main aim was to investigate specific between-group effects while maintaining control of key demographic variables that are typically associated with reporting physical, cognitive, and emotional symptoms associated with PPCS. Given that there were no between-group differences in age, sex, or education and the groups have been found to be similar regarding a range of psychosocial variables, 44 there is no obvious reason to believe that recruitment bias is a driver of the results supporting our main conclusion.…”
Section: Discussionsupporting
confidence: 66%
“…Our main aim was to investigate specific between-group effects while maintaining control of key demographic variables that are typically associated with reporting physical, cognitive, and emotional symptoms associated with PPCS. Given that there were no between-group differences in age, sex, or education and the groups have been found to be similar regarding a range of psychosocial variables, 44 there is no obvious reason to believe that recruitment bias is a driver of the results supporting our main conclusion.…”
Section: Discussionsupporting
confidence: 66%
“…The control group was found to be comparable to the mTBI group on a broad range of personal factors. 40 The study was approved by the regional committee for research ethics (REK 2013/754), and participants and parents of participants younger than 18 years gave informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…PPCS was defined as having ≥ 3 core symptoms rated at least moderate (score ≥ 3), or a total score of 13-52 (i.e., 52 is the highest possible score). 40…”
Section: Persistent Postconcussion Symptomsmentioning
confidence: 99%
“…[11][12][13][14] Studies of mild TBI (mTBI) have suggested that outcomes are impacted by pre-TBI sociodemographics, use of alcohol and tobacco, prior TBIs, and presence of psychiatric and neurological diseases. 11,[15][16][17][18][19][20] In particular, individuals with pre-existing migraine have reported greater and different post-concussive symptoms and had worse verbal and visual memory within the first 72 h after concussion measured by Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) compared to individuals who did not have pre-existing migraine. 14 In another study the presence of pre-TBI headache/migraine predicted greater disability, sleep problems, and emotional symptoms at 3 months post mTBI, and physical post-concussive symptoms at 6 months post-TBI.…”
Section: Introductionmentioning
confidence: 99%